Irony & Ecstasy : Contemporary American Paintings and Drawings - Kierkegaard, Soren; Ottmann, Klaus (London : Salama-Caro Gallery, 1993)
Beyt, Mary ; Curtis, Margaret ; Diamond, Jessica ; Dona, Lydia ; Evans, Steven ; Hopkins, Peter ; Howe, Catherine ; Hyde, James ; Laramée, Eve Andrée ; Laudi, Jane ; Lifschutz, Scott ; Lomberg, Jody ; Marcaccio, Fabian ; McClelland, Suzanne ; Ostendarp, Carl ; Pettibon, Raymond ; Pierson, Jack ; Rule, Nicolas ; Wayne, Leslie ; Williams, Megan
biografie
Irony & Ecstasy : Contemporary American Paintings and Drawings, Salama-Caro Gallery, London, 21 April - 29 May 1993
Engels
boek